Pengenalan Kesejahteraan Hewan sejak Dini pada Tarbiyatul Athfal Hidayatul Mubtadiin Malang secara Daring - Permata, Fajar Shodiq; Pranata, Verel Welly Adrian; Paramanandi, Dini Agusti (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: This community service activity aimed to provide an early introduction to animal welfare at TA (Tarbiyatul Athfal) Hidayatul Mubtadiin Malang via online. Methodology: Community service activities were conducted online with 13 participants as 6 years old as second level from TA Hidayatul Mubtadiin Malang, East Java. Before online learning, students were given worksheets (cognitive and numerical English) related to rabbit behavior and the introduction of animal welfare in rabbits. Students fill in worksheets at the same time as the online learning process. After learning, parents were asked to provide responses to questionnaires related to satisfaction with implementing activities. Recaps of TA students' responses and worksheets are then analyzed descriptively using pie charts. Results: The worksheet showed that TA students could do well in cognitive (80-100 score is 85%) and numeric English (80-100 score is 100%). Parents responded very well (54-69%) and good (23-46%). Online methods for early animal welfare recognition in TA students can work well through learning media technology such as presentations and videos. Conclusions: The online method for early animal welfare introduction to students of Tarbiyatul Athfal (TA) Hidayatul Mubtadiin Malang can run effectively through the use of educational media technologies such as presentations and videos. Limitations: The limitations of the service were that the meeting was conducted once, and students' supervised parents gave the answering-answer sheet. Contribution: Community service contributes to introducing animal welfare in the early stage of education at the kindergarten level that wishes to elevate their respect for animal.